Mathematical statistics exercises and solutions - Shao Jun (New York Springer-Verlag, 2005)
This textbook covers topics in statistical theory essential for graduate students preparing for work on a Ph.D. degree in statistics. On the other hand, this is a stand-alone book, since exercises and solutions are comprehensible independently of their s
Keywords: Mathematical statistics